Globalizations and emerging issues in trade theory and policy - Beladi, Hamid; Choi, Kwang, 1947-; Tran-Nam, Binh, 1954-; Long, Ngo Van; Tawada, Mokoto; Atax, Binh Tran-Nam (Emerald, 2008)
This edited volume is a collection of latest research findings on topical issues in international trade theory and policy. The chapters are contributed by well known academic economists around the globe as a tribute to Professor Murray Kemp's 80th birthday. They cover three broad areas of globalization and emerging issues in international trade. The first part of the volume, containing five chapters, deals with trade liberalization and outsourcing. These chapters examine the role of the WTO, trade liberalization as a game under uncertainty, a Chamberlinian-Ricardian model, liberalization of government procurements, and outsourcing and import restriction policies. The second part of the volume, also containing five chapters, examines trading clubs and preferential trading agreements. These chapters extend the original Kemp-Wan proposition concerning customs unions in various directions.The final part of this book consists of six chapters on various aspects of trade and aid. These include a review of Kemp's contributions to trade and welfare economics, gains from trade and refusal to trade, increasing returns and oligopoly, tariff policy and foreign economic aid, infrastructure aid and deindustrialization, and environmental regulation and tourism.
Includes index.
Keywords: International economic relations.; elektronické knihy; electronic books